Aplikasi Bejakeun sebagai Optimalisasi Sarana Pelaporan dan Upaya Preventif Tindakan Bullying di SMP Negeri 43 Kota Bandung - Ilham Pauji; Iwan Sanusi (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study aims to describe the use of the Bejakeun application (Dare to oppose bullying, Protect yourself and your friends from bullying, Recognize and report, Upload reports) as a means of reporting and preventing bullying at SMP Negeri 43 Bandung City. This Android-based application, available on the Play Store, features anonymous reporting, allowing students to report without identifying themselves, thereby reducing the fear of intimidation or direct involvement. The study used a qualitative approach with descriptive methods. Data were obtained through documentation, interviews, and observations of the application's implementation process. The results indicate that Bejakeun strengthens the reporting system previously implemented through WhatsApp and Google Forms and contributed to a decrease in the number of bullying cases, from 25 cases (2023/2024) to 14 cases in the 2024/2025 academic year. The application is also integrated with positive habituation programs at the school, such as flag ceremonies, Quran recitation, literacy, morning exercise, and Dhuha prayer, creating a more comprehensive approach to bullying prevention. Bejakeun has received recognition from the city level to the Asia Pacific regional championship, demonstrating its potential as a good practice worthy of replication in other educational institutions.